2010
DOI: 10.1007/s10096-010-1032-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated sICAM-1 levels in patients with hemorrhagic fever with renal syndrome caused by Hantaan virus

Abstract: Increased vascular permeability and vascular leakage are characteristic pathological changes in hemorrhagic fever with renal syndrome (HFRS). Vascular endothelial cells are the main targets of Hantaan virus, the etiological agent of the severe form of HFRS. Hantaan virus can induce extensive damage of small blood vessels and capillaries. In vitro infection of human umbilical vein endothelial cells by Hantaan virus can induce the expression of intercellular adhesion molecule-1 (ICAM-1). The involvement of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…Similar evidence for endothelial damage came from a study of Dengue patients with higher plasma levels of sVCAM-1 than the control groups (Murgue, Cassar et al 2001;Cardier, Rivas et al 2006). The levels of sICAM-1 were also shown to be higher in patients with hemorrhagic fever with renal syndrome (HFRS) caused by Hantaan virus (Han, Zhang et al 2010).…”
Section: Endothelial Cells In Cchf Pathogenesissupporting
confidence: 60%
“…Similar evidence for endothelial damage came from a study of Dengue patients with higher plasma levels of sVCAM-1 than the control groups (Murgue, Cassar et al 2001;Cardier, Rivas et al 2006). The levels of sICAM-1 were also shown to be higher in patients with hemorrhagic fever with renal syndrome (HFRS) caused by Hantaan virus (Han, Zhang et al 2010).…”
Section: Endothelial Cells In Cchf Pathogenesissupporting
confidence: 60%
“…These mediators alter the vascular function and trigger coagulation disorders [Marty et al, 2006]. For example, hantavirus is able to infect endothelial cells directly and induce the production of chemokines and cell adhesion molecules like IL‐8, IL‐6, GRO‐β, and ICAM [Song et al, 1999; Geimonen et al, 2002; Han et al, 2008]. Levels of von Willebrand factor and soluble tissue factor are increased in patients with severe dengue infection [Sosothikul et al, 2007], while upregulation of tissue factor transcription has also been reported [Huerta‐Zepeda et al, 2008].…”
Section: Methodsmentioning
confidence: 99%
“…Endothelial cell activation occurs in HFRS. Upregulated levels of soluble EC receptors: E-Selectin ( Takala et al, 2000 ), intercellular adhesion molecule (ICAM; Han et al, 2010 ), and tumor necrosis factor receptor (TNFR)-1 ( Kyriakidis and Papa, 2013 ) are released into circulation during acute HFRS. While there is no evidence on EC activation in HCPS, the upregulation of pro-inflammatory cytokines: interleukin (IL)-6, tumor necrosis factor (TNF)-α, and interferon (IFN-γ) that all are capable of activating the endothelium, have been reported in both hantavirus diseases ( Linderholm et al, 1996 ; Peters et al, 1999 ; Klingstrom et al, 2002 ; Abel Borges and Figueiredo, 2008 ; Sadeghi et al, 2011 ; Saksida et al, 2011 ; Korva et al, 2013 ; Kyriakidis and Papa, 2013 ).…”
Section: Inflammationmentioning
confidence: 99%